A prospective cohort study of fetal heart rate monitoring: deceleration area is predictive of fetal acidemia - Cahill, Alison G.; Tuuli, Methodius G.; Stout, Molly J.; López, Julia D.; Macones, George A. (American journal of obstetrics and gynecology, 2018)
Intrapartum electronic fetal monitoring is the most commonly used tool in obstetrics in the United States; however, which electronic fetal monitoring patterns predict acidemia remains unclear. This study was designed to describe the frequency of patterns seen in labor using modern nomenclature, and to test the hypothesis that visually interpreted patterns are associated with acidemia and morbidities in term infants. We further identified patterns prior to delivery, alone or in combination, predictive of acidemia and neonatal morbidity. This was a prospective cohort study of 8580 women from 2010 through 2015. Patients were all consecutive women laboring at ≥37 weeks’ gestation with a singleton cephalic fetus. Electronic fetal monitoring patterns during the 120 minutes prior to delivery were interpreted in 10-minute epochs. Interpretation included the category system and individual electronic fetal monitoring patterns per the Eunice Kennedy Shriver National Institute of Child Health and Human Development criteria as well as novel patterns. The primary outcome was fetal acidemia (umbilical artery pH ≤7.10); neonatal morbidities were also assessed. Final regression models for acidemia adjusted for nulliparity, pregestational diabetes, and advanced maternal age. Area under the receiver operating characteristic curves were used to assess the test characteristics of individual models for acidemia and neonatal morbidity. Of 8580 women, 149 (1.7%) delivered acidemic infants. Composite neonatal morbidity was diagnosed in 757 (8.8%) neonates within the total cohort. Persistent category I, and 10-minute period of category III, were significantly associated with normal pH and acidemia, respectively. Total deceleration area was most discriminative of acidemia (area under the receiver operating characteristic curves, 0.76; 95% confidence interval, 0.72–0.80), and deceleration area with any 10 minutes of tachycardia had the greatest discriminative ability for neonatal morbidity (area under the receiver operating characteristic curves, 0.77; 95% confidence interval, 0.75–0.79). Once the threshold of deceleration area is reached the number of cesareans needed-to-be performed to potentially prevent 1 case of acidemia and morbidity is 5 and 6, respectively. Deceleration area is the most predictive electronic fetal monitoring pattern for acidemia, and combined with tachycardia for significant risk of morbidity, from the electronic fetal monitoring patterns studied. It is important to acknowledge that this study was performed in patients delivering ≥37 weeks, which may limit the generalizability to preterm populations. We also did not use computerized analysis of the electronic fetal monitoring patterns because human visual interpretation was the basis for the Eunice Kennedy Shriver National Institute of Child Health and Human Development categories, and importantly, it is how electronic fetal monitoring is used clinically.